FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI ( Studi Di Kelurahan Sungai Jawi Dalam Kecamatan Pontianak Barat Kota Pontianak) - Aditya E.21111104, Lismi (FISIP Universitas Tanjungpura, 2013)
The quality of employee performance depends on several factors. These factors help each employee in achieving their achievment in working. In reality, the local government faced some difficulties in doing their duty and responsibility, such as low competitive profesionalism, low human resource and work ethic, and lack of facilities. Therefore the local government service lack of integrity. This focus of research will be described by using qualitative method with case study in West Pontianak. The research is focus to describe what factors that cann decrease the employee performance in Kelurahan Sungai Jawi Dalam Kecamatan Pontianak Barat. The result of this research showed that there are 3 factors which affected the decreasing of employee performance, they are the skill of the human resource which connected to the quality of the human resource itself, the facilities including all tools, work equipments, and other facilities that has important function and aso the environment along with the internal factors, external factors, working culture and discipline.Â Keywords: Performance employee, human resources, facilities, organization environment.